Towards the preparation of synthetic outer membrane vesicle models with micromolar affinity to wheat germ agglutinin using a dialkyl thioglycoside - Dimitri Fayolle; Nathalie Berthet; Bastien Doumeche; Olivier Renaudet; Peter Strazewski; Michele Fiore (Beilstein Journal of Organic Chemistry, 2019)
A series of alkyl thioglycosides and alkyl thiodiglycosides bearing glucose and N-acetylglucosamine residues were prepared by thiol–ene coupling in moderate to good yields (40–85%). Their binding ability towards wheat germ agglutinin was measured by competitive enzyme-linked lectin assays. One of the synthetic compounds presenting two GlcNAc units showed the highest inhibitory effect of this study with an IC50 of 11 µM corresponding to a 3182-fold improvement compared to GlcNAc. These synthetic molecules were used to produce giant vesicles, alone or in mixture with phospholipids, mimicking bacterial outer membrane vesicles (OMV) with potential antiadhesive properties.